Could someone pls show me why:
(m/(n+m))*(V+mK) - mK
is equivalent to:
(m/(n+m))*(V-nK)
Thx for the help
Ben
Let's play algebra.
{(m/(n+m))*(V+mK) - mK} =? {(m/(n+m))*(V-nK)}
Notice that [m / (m+n)] is common to both expressions. So we eliminate that to simplify the two expressions. Divide both sides by [m / (m+n)],
(V +mK) -(mK / [m /(m+n)]) =? V -nK
Then simplify. Expand the Lefthand Side,
(V +mK) -(mK * [(m+n) / m]) =? V -nK
(V +mK) -[(mK)(m+n) / m] =? V -nK
Clear the fraction, multiply both sides by m,
m(V +mK) -mK(m+n) =? mV -mnK
mV +(m^2)K -(m^2)K -mnK =? mV -mnK
mV -mnK =? mV -mnK
Yes.
So, it is shown.